Indicators of socio-environmental vulnerability: measurement and evaluation for the Capital of Paraíba, Brazil (Research, Society and Development, 2020)
The theme of socio-environmental vulnerability in the urban context involves the social issues of a population, as well as the environmental dimension. In this sense, this article aims to analyze the socio-environmental vulnerability of the city of João Pessoa - PB. Therefore, it was based on the set of indicators proposed by Vasconcelos et al. (2019), for constituting a set that addresses social and environmental aspects to characterize Brazilian cities. An exploratory and descriptive study was carried out, through bibliographic and documentary research, as well as in the choice and collection of data for the indicators for the capital of Paraíba. The results demonstrate that João Pessoa's level of socio-environmental vulnerability is classified as ‘High’. This result is considered unsatisfactory and worrying, as it puts the city in a problematic situation, demanding needs so that it is possible to guarantee the quality of life of local citizens. Therefore, demanding from the State a more complete planning so that it can guide its actions regarding the provision of public services, so that it guarantees and protects the interests of the entire population. However, the authorities will be able to use the present study as an aid tool in solving the problems that place the citizens in a situation of socio-environmental vulnerability. In addition, the article allows for future studies to structure planning and improve urban management.